Evolutionary divergence of the cytochrome b[[5]] gene of Drosophila. - Kula, M.E.; Allay, E.R.; Rozek, C.E. (Journal of Molecular Evolution, 1995)
Cytochrome proteins perform a broad spectrum of biological functions ranging from oxidative metabolism to electron transport and are thus essential to all organisms. The b-type cytochrome proteins bind heme noncovalently, are expressed in many different forms and are localized to various cellular compartments. We report the characterization of the cytochrome b5 (Cyt-b) gene of Drosophila virilis and compare its structure to the Cyt-b gene of Drosophila melanogaster. As in D. melanogaster, the D. virilis gene is nuclear encoded and single copy. Although the intron/exon structures of these homologues differ, the Cyt-b proteins of D. melanogaster and D. virilis are approximately 75% identical and share the same size coding regions (1,242 nucleotides) and protein products (414 amino acids). The Drosophila Cyt-b proteins show sequence similarity to other b-type cytochromes, especially in the N-terminal heme-binding domain, and may be targeted to the mitochondrial membrane. The greatest levels of similarity are observed in areas of potential importance for protein structure and function. The exon sequences of the D. virilis Cyt-b gene differ by a total of 292 base changes. However, 62% of these changes are silent. The high degree of conservation between species separated by 60 million years of evolution in both the DNA and amino acid sequences suggests this nuclear cytochrome b5 locus encodes an essential product of the Drosophila system.